Active damping of DC power networks - Jusoh, Awang (2003)
The research involves devising new control and compensation methods for DC power distribution systems containing power electronics loads with constant power characteristic. A compensation method called an active damping network is examined, which utilises capacitor and inductor energy storage elements and high frequency switching devices. This network is controlled to behave as a small-signal resistor so that any instabilities in the power distribution system due to the interaction between interconnected sub-systems will be damped and eliminated successfully. This method is studied and analysed in detail. The system was designed and simulated, and was verified by experimental results. The results show that stable operation is achieved of a small-scale power distribution system that contains power electronic loads with constant power characteristics such as DC-DC converters and electrical drives.